2017
DOI: 10.3727/096368916x693662
|View full text |Cite
|
Sign up to set email alerts
|

Human Muse Cells, Nontumorigenic Phiripotent-Like Stem Cells, Have Liver Regeneration Capacity through Specific Homing and Cell Replacement in a Mouse Model of Liver Fibrosis

Abstract: Muse cells, a novel type of nontumorigenic pluripotent-like stem cells, reside in the bone marrow, skin, and adipose tissue and are collectable as cells positive for pluripotent surface marker SSEA-3. They are able to differentiate into cells representative of all three germ layers. The capacity of intravenously injected human bone marrow-derived Muse cells to repair an immunodeficient mouse model of liver fibrosis was evaluated in this study. The cells exhibited the ability to spontaneously differentiate into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(99 citation statements)
references
References 42 publications
(81 reference statements)
2
91
0
Order By: Relevance
“…The SDF-1-CXCR4 axis may also be a candidate factor that triggers Muse cell mobilization. However, it has been already reported that CXCR4 antagonist AMD3100 in animal serum could only partially suppress Muse cell migration towards the damaged liver, and its suppression effect did not differ significantly between Muse and non-Muse cells, 15 suggesting that the effect of SDF-1 on mobilizing Muse cells is smaller than that of S1P.…”
Section: Remodeling and Muse Cell Numbermentioning
confidence: 86%
“…The SDF-1-CXCR4 axis may also be a candidate factor that triggers Muse cell mobilization. However, it has been already reported that CXCR4 antagonist AMD3100 in animal serum could only partially suppress Muse cell migration towards the damaged liver, and its suppression effect did not differ significantly between Muse and non-Muse cells, 15 suggesting that the effect of SDF-1 on mobilizing Muse cells is smaller than that of S1P.…”
Section: Remodeling and Muse Cell Numbermentioning
confidence: 86%
“…Muse cells were originally identified as cells that are resistant to long-term trypsin incubation and are known as cells that are double positive for the pluripotent surface marker, stage-specific embryonic antigen-3 (SSEA-3), and CD105, and that have the capacity for self-renewal and triploblastic differentiation from a single cell [6]. The applicability of Muse cells for regenerative treatments has been suggested in disease models of liver damage, stroke, skin ulcers related to diabetes mellitus, and osteochondral defects [9], [10], [11], [12].…”
Section: Introductionmentioning
confidence: 99%
“…Muse cells also harbor the ability to home into the liver in a fulminant hepatitis mouse model replenishing new cells and contributing to tissue repair [8]. Muse cells migrate and integrate into damaged liver in a liver fibrosis mouse model [16]. Fibrotic liver area and serum total bilirubin are decreased, while serum total albumin is increased, demonstrating functional restoration [16].…”
Section: Muse Cells and Tissue Regenerationmentioning
confidence: 99%
“…They exist normally in a quiescent state and are activated when exposed to conditions of severe cellular stress both in vitro and in vivo [5, 79, 14]. In contrast to ESCs and iPSCs, Muse cells exhibit telomerase activity and asymmetric growth and thus do not undergo tumorigenesis or teratoma formation when transplanted into a host organism (Figures 2(a), 2(b), 2(d), and 2(e)) [5, 79, 1416]. Muse cells also exhibit a normal karyotype, as they demonstrate normal chromosome number and integrity (Figure 2(i)).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation